Characterization Of Two Cellulosic Waste Materials (Orange And Almond Peels) And Their Use For The Removal Of Methylene Blue From Aqueous Solutions - Boumediene, M.; Benaïssa, H.; George, B.; Molina, St.; Merlin, A. (Maderas. Ciencia y Tecnología, 2015)
The ability of orange peels (OP) and almond peels (AP) as adsorbents for the removal of a dyestuff, namely methylene blue (MB) from aqueous solutions has been studied. After their characterization by different techniques (elemental analysis, biochemical analysis, IR spectroscopy, thermogravimetric analysis, scanning electron microscopy, mercury porosimetry), adsorption kinetics of the dye have been investigated using common kinetic models cited in the literature: first order and pseudo-second order. The correlation coefficient has showed that the pseudo-second order kinetic equation best describes the adsorption kinetics for the tested materials. The experimental equilibrium data have been analyzed using linearized forms of Langmuir and Freundlich isotherms. The Langmuir isotherm was found to provide the best theoretical correlation of the experimental data whatever the biosorbents tested. Using the equilibrium coefficients obtained at different temperatures, various thermodynamic parameters such as ΔG°, ΔH°, ΔS° have been calculated. The thermodynamics of MB/OP and MB/AP systems indicated spontaneous and endothermic process. It was concluded that an increase in temperature results in a higher MB loading per unit weight of OP or AP.